Common Variable Immunodeficiency and Circulating TFH - Ana Coraglia; Nora Galassi; Diego S. Fernández Romero; M. Cecilia Juri; Marta Felippo; Alejandro Malbrán; María M. E. de Bracco (Journal of Immunology Research)
CD4+ T follicular helper cells (TFH) were assessed in adult patients with common variable immune deficiency (CVID) classified according to the presence of granulomatous disease (GD), autoimmunity (AI), or both GD and AI (Group I) or the absence of AI and GD (Group II). TFH lymphocytes were characterized by expression of CXCR5 and PD-1. TFH were higher (in both absolute number and percentage) in Group I than in Group II CVID patients and normal controls (N). Within CXCR5+CD4+ T cells, the percentage of PD-1 (+) was higher and that of CCR7 (+) was lower in Group I than in Group II and N. The percentages of Treg and TFH reg were similar in both CVID groups and in N. TFH responded to stimulation increasing the expression of the costimulatory molecules CD40L and ICOS as did N. After submitogenic PHA+IL-2 stimulation, intracellular expression of TFH cytokines (IL-10, IL-21) was higher than N in Group I, and IL-4 was higher than N in Group II. These results suggest that TFH are functional in CVID and highlight the association of increased circulating TFH with AI and GD manifestations.